Rockstar Games, Red Dead Redemption, and Narratives of “Progress” - Esther Wright (European Journal of American Studies)
In both popular and historiographical discussions of the nineteenth- and twentieth-century American West, and the successive waves of popular culture that have come to represent Westward expansion and colonization, there has been much negotiation and debate over the nature and meaning of “progress.” Usually bound up with other loaded terms such as “civilization” (and its implicit antithesis, “savagery”), popular culture that falls under the broader umbrella of the Western genre has often used the idea of progress and development, from past to future, as a cornerstone of their stories and messages. This article uses game developer Rockstar Games and the company’s popular and commercially successful Red Dead Redemption franchise (2010-2018) to examine how narratives of “progress” have been used by the company not only to create their own representations of US history but, moreover, to prop up the promotional discourses that the company uses to brand themselves and sell their products. Ultimately, this article explores the tensions between a company that claims to offer games that are both “authentic” and critical of turn-of-the-century US history and culture, yet which implicitly rely on the ideologies that accompany narratives of “progress” and “civilization,” bound up as they are with the Frontier myth, white supremacy, and colonialism.